From: album 23. Dedication by Jourde to G. Lefrançais, dated June 3, 1876, on back. Text on back: 'Comptable-Délégué aux Finances sous la Commune' - Schweitzer, Emile,
From: album 23. Dedication by Jourde to G. Lefrançais, dated June 3, 1876, on back. Text on back: 'Comptable-Délégué aux Finances sous la Commune'.